Crop productivity and environmental attributes in Jodhpur district of western Rajasthan (MAUSAM, 1985)
The study deals with crop yields of bajra, kharif pulses and sesamum in relation to rainfall, mean relative humidity and mean temperature in Jodhpur district of western Rajasthan. Highest instability was observed in order to sesamum, bajra and kharif pulses, while mean relative humidity and mean temperature were more stable. Multivariate analysis showed that yield of crops  under study were positive and significantly influenced by rainfall and negatively by mean temperature an Mon- barring bajra crop. The mean relative humidity had weak influence on crop productivity and significant at lower level. The order of variables were rainfall, mean relative humidity and mean temperature, for bajra and kharif pulses while for sesamum order was rainfall, mean temperature and mean relative humidity. Therefore, to increase the yield of crops, technological changes like use of fertilizer and HYV seeds more tolerant to temperature should be popularized.